(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2024)
The objective of this project was to carry out a socio-environmental evaluation of post-harvest coconut waste in Portoviejo, Tosagua and Rocafuerte. The Participatory Rapid Diagnosis was used in two stages: collection of information through surveys, sampling and technical visits to producing farms, georeferencing of data and generation of proposals. The study determined that the most planted coconut variety was the giant (56%) with around 1 to 3 ha with between 500 to 800 plants/ha, its production ranges between 800 to 1000 coconuts per harvest, whose residues are disposed of to the collector. (46%), they burn (28%), and 74% of producers do not carry out good environmental practices on their farms. Rocafuerte is the canton with the highest generation (96.31%), followed by Tosagua (2.64%) and Portoviejo with 1.05% of the total. It is necessary to promote the awareness of producers regarding the potential use of coconut waste under a circular economy approach.